2020
DOI: 10.1016/j.clim.2020.108487
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 hypersensitivity in COVID-19 vasculitis

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
144
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 10 publications
6
144
0
4
Order By: Relevance
“…Similarly, blockage of IL-6 and granulocyte macrophage-colony stimulating factor inhibits monocyte-macrophage recruitment and differentiation to the lungs, and blocks the inflammatory response ( Gómez-Rial and Martinón-Torres, 2020 ). In addition to that, deposition of immune complexes (ICs) inside vascular walls can also induce cytokine storm ( Roncati et al, 2020 ) hence status of ICs may be too critical for design and immune-based treatments like plasma therapy and vaccine ( Vuitton et al, 2020 ). To make the situation more complicated, there is an activation of complement C3 during lung injury, and C3-targeted intervention by compstatin-based complement C3 inhibitor AMY-101 prevents complement-mediated inflammatory damage in COVID-19 patients ( Mastaglio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, blockage of IL-6 and granulocyte macrophage-colony stimulating factor inhibits monocyte-macrophage recruitment and differentiation to the lungs, and blocks the inflammatory response ( Gómez-Rial and Martinón-Torres, 2020 ). In addition to that, deposition of immune complexes (ICs) inside vascular walls can also induce cytokine storm ( Roncati et al, 2020 ) hence status of ICs may be too critical for design and immune-based treatments like plasma therapy and vaccine ( Vuitton et al, 2020 ). To make the situation more complicated, there is an activation of complement C3 during lung injury, and C3-targeted intervention by compstatin-based complement C3 inhibitor AMY-101 prevents complement-mediated inflammatory damage in COVID-19 patients ( Mastaglio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Necrotizing vasculitis has been described as a common histopathological nding in SARS-CoV-2 infected patients [4], with typical features. Enteric and bowel involvement, however, is not yet clear: some authors suggest it is present in up to 50% of the cases [5]. Furthermore, SARS-Cov-2 has been detected in samples from faeces suggesting that virus can actively infect and replicate in the GI tract [6] leading to different forms of colitis; a common feature for the other member of coronavirus family.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SARS-Cov-2 has been detected in samples from faeces suggesting that virus can actively infect and replicate in the GI tract [6] leading to different forms of colitis; a common feature for the other member of coronavirus family. Nowadays, exact mechanism of viral infection causing intestinal symptomatology is not yet understood, Angiotensin-Converting Enzyme 2 (ACE 2) receptor, known as the SARS CoV-2 receptor on human, is expressed not only by lung but also by intestinal epithelium: mouse models shows that ACE2 receptor modi cations can be associated with higher rate in colitis, suggesting that receptor modi cation due to virus infection can increase risk of developing intestinal in ammation and colitis [5]. It is also known that COVID-19 patient, especially with more severe forms of disease, suffered for an acute systemic in ammatory response due to cytokine storms that can develop a multiple organs injury [7], often driven by vasculitis as initial damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roncati et al reported scientific evidence that in COVID-19, vasculitis indicates that a life-threatening escalation and switch from humoral immunity (type 2 T-helper immune response) to type 3 hypersensitivity has taken place. The deposition of immune complexes inside the vascular walls could induce a severe inflammatory state with the consequent inflammatory amplification ascribed as cytokine storm syndrome [120] . Type 3 hypersensitivity represents an immunopathogenic mechanism of disease that involves immune complexes deposition inside tissues and blood vessels, inducing a severe inflammatory state by the action of complement anaphylatoxins (C3a and C5a) that ultimately leads to tissue damage.…”
Section: Introductionmentioning
confidence: 99%